A third of nonfasting plasma cholesterol is in remnant lipoproteins: Lipoprotein subclass profiling in 9293 individuals. (July 2019) - Balling, Mie; Langsted, Anne; Afzal, Shoaib; Varbo, Anette; Davey Smith, George; Nordestgaard, Børge G.
Abstract: Background and aims: Increased concentrations of calculated remnant cholesterol in triglyceride-rich lipoproteins are observationally and genetically, causally associated with increased risk of ischemic heart disease; however, when measured directly, the fraction of plasma cholesterol present in remnant particles is unclear. We tested the hypothesis that a major fraction of plasma cholesterol is present in remnant lipoproteins in individuals in the general population. Methods: We examined 9293 individuals from the Copenhagen General Population Study using nuclear magnetic resonance spectroscopy measurements of total cholesterol, free- and esterified cholesterol, triglycerides, phospholipids, and particle concentration. Fourteen subclasses of decreasing size and their lipid constituents were analysed: six subclasses were very low-density lipoprotein (VLDL), one intermediate-density lipoprotein (IDL), three low-density lipoprotein (LDL), and four subclasses were high-density lipoprotein (HDL). Remnant lipoproteins were VLDL and IDL combined. Results: Mean nonfasting cholesterol concentration was 1.84 mmol/L (72 mg/dL) for remnants, 2.01 mmol/L (78 mg/dL) for LDL, and 1.83 mmol/L (71 mg/dL) for HDL, equivalent to remnants containing 32% of plasma total cholesterol. Of 14 lipoprotein subclasses, large LDL and IDL were the ones containing most of plasma cholesterol. The plasma concentration of remnant cholesterol was from ∼1.4 mmol/L (54 mg/dL) at age 20 to ∼1.9 mmol/L (74 mg/dL) at age 60. Corresponding values for LDL cholesterol were from ∼1.5 mmol/L (58 mg/dL) to ∼2.1 mmol/L (81 mg/dL). Conclusions: Using direct measurements, one third of total cholesterol in plasma was present in remnant lipoproteins, that is, in the triglyceride-rich lipoproteins IDL and VLDL. Graphical abstract: Image 1 Highlights: Using NMR, a third of plasma cholesterol was present in remnant lipoproteins. Of 14 lipoprotein subclasses, large LDL and IDL were containing most cholesterol. Directly measured remnant cholesterol was highest in older individuals.